KEN ANGROK PENDIRI WANGŚA RĀJASA - Firmasyah, Defan; Yahmin, Yahmin (Maharsi: Jurnal Pendidikan Sejarah dan Sosiologi, 2019)
This research have a purpose to reveal Ken Angrok’s figure in establish Tumapĕl’s Kingdom and also Wangśa Rājasa’s cause Ken Angrok establish this family’s name in 13th Century. In this research, have a research’s methods can be use, that is historiography’s methods. Historiography’s methods consist of four stage. This stage is: 1) Heuristic (aggregation of data source, that is ancient inscription, manuscript, foreign’s report and folklore); 2) Criticical Source (verify to accurate data source); 3) Interpretation (declension to various sata source); and 4) Historriography (writing about result’s research into form about scientific activities). This research can be conclusion that is Ken Angrok succesfull fall out Kaḍiri’s Kingdom and establish his kingdom and the new dynasty’s name. Successful from Ken Angrok because the right political strategy and with support from the clergy, the leader from local’s area and the leader from vilages in the east Kawi’s Mountain and the legitimacy from politics pass through his wedding with Ken Dĕḍĕs.